Analisis Penerapan cara Produksi Pangan yang Baik (CPPB) pada Industri Rumah Tangga Pangan di Kecamatan Borong Kabupaten Manggarai Timur - Anita, Maria Fianney; Wahyuni, Ike Dian; Yuniastuti, Tiwi (Poltekkes Kemenkes Bengkulu, 2025)
Good Food Production Practices (GMP) are guidelines or minimum standards for food producers and home food industries to ensure safe, high-quality, and consumable products. However, many home food industries in Borong District have not yet implemented GMP, so research is needed to improve food quality in the district. This study aims to determine the level of implementation of GMP in four Home Food Industries (IRTP) in Borong District, East Manggarai Regency. This study employed a qualitative descriptive method, with data collection techniques including observation, interviews, documentation, and literature review, referring to the Regulation of the Head of the Indonesian Food and Drug Authority (BPOM RI) No. HK.03.1.23.04.12.2206 of 2012 concerning Good Manufacturing Practices (GMP) for Food Processing and Processing Industry (GMP-IRT). The informants were the home food industries Ma Ren Keripik, Nendong, Teko Nggeruk, and De Martin Keripik at Borong District. The study results shows that the implementation of Good Manufacturing Practices (GMP) at the four GMPs remains low, with a percentage of non-compliance of 52% for Ma Ren Keripik, 56% for Nendong, 56% for Teko Nggeruk, and 62% for De Martin Keripik, respectively. The most frequent non-compliance is found in aspects of buildings and facilities, hygiene and sanitation, process control, and record-keeping and documentation. This indicates that business operators still lack a thorough understanding of Good Manufacturing Practices (GMP) and have not fully implemented food safety principles according to applicable standards, due to educational background, limited time, energy, and funds, as well as minimal oversight from relevant government agencies. It can be concluded that the implementation of Good Manufacturing Practices (GMP) at the home food industry in Borong District is not yet optimal. It requires increased education, training, and on going supervision by relevant government agencies to ensure the quality and safety of the resulting food products.